Evaluasi Penerapan Sistem Manajemen Keselamatan Pertambangan (SMKP) di IUP 206 Ha Batu Gamping, PT Semen Padang, Sumatra Barat - Risma Erwi Gusvita; Fadhilah Fadhilah; Heri Prabowo; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2023)
At the mining company PT Semen Padang there are still several cases of work accidents and a decrease in the achievement level of SMKP audits in 2022, especially in the 206 Ha Limestone IUP by 69%. This study aims to analyze work accident statistics for 2021-2022 and evaluate the implementation of SMKP in IUP 206 Ha Batu Gamping, PT Semen Padang in 2023. This research is an evaluation design study with a quantitative descriptive approach. Data collection techniques started from literature studies, questionnaires, review of documents & records, observations and interviews. The results showed that there was an increase in the frequency of accidents (FR) and the severity of accidents (SR). In 2021 the FR and SR values are 0 while in 2022 the FR values are 0.51 and the SR values are 3.60. The results of the questionnaire analysis related to the implementation of SMKP in IUP 206 Ha in 2023 show an increase with a compliance percentage value of 81% using a Likert scale calculation. The elements that must be improved are Element IV Implementation, Element VI Documentation and Element VII Management review & performance improvement.